Control de los costos de producción y su impacto en la rentabilidad en el sector camaronero. - Lituma Cango, Ruth Raquel; Narvaez Medina, Maria Jose (Universidad Técnica de Machala, 2022)
Currently, the shrimp activity in our country is one of the main economic supports that it has internally. Entrepreneurs in the shrimp sector need to know qualitatively and quantitatively those inputs, resources and elements that will need to be incurred so that their activity generates future benefits. Therefore, accounting is adapted to the shrimp activity, providing reliable and timely information that allows making the right decisions. The general objective of the research is: To determine the production costs and their effect on the profitability of the shrimp sector. For Ecuador, the exports of the shrimp sector play a very important role for decades, in this way it has been developing efficiently, optimizing costs and exports. The methodology responds to a quantitative and qualitative approach. From the quantitative approach it is expected to be as objective as possible from the quantification of the results obtained during the investigation and from the qualitative approach, it is based on an interpretive perspective focused on the understanding of the meaning of the actions, seeking to interpret the results obtained. to the context of the studied problem. The importance of determining the profitability analysis stems from the multiple goals of companies, whether they are based on profit, or those based on stability, development or service to the community, the analysis of benefits, the dispute it tends to be at the center of the discussion as a fundamental variable of economic activity.
Actualmente, la actividad camaronera, en nuestro país, se sitúa como uno de los principales sustentos económicos que internamente este posee. Los empresarios del sector camaronero, requieren conocer de forma cualitativa y cuantitativa aquellos insumos, recursos y elementos en los que se necesitará incurrir para que su actividad genere beneficios futuros. Por ende, la contabilidad se adapta a la actividad camaronera brindando información confiable y oportuna que permita tomar decisiones acertadas. El objetivo general de la investigación es: Determinar los costos de producción y su efecto en la rentabilidad del sector camaronero. Para el Ecuador las exportaciones del sector camaronero juegan un rol muy importante durante décadas, de este modo se ido desarrollando de manera eficaz haciendo que los costos y exportaciones se optimicen. La metodología responde a un enfoque cuantitativo y cualitativo. Desde el enfoque cuantitativo se espera ser lo más objetivo posible a partir de la cuantificación de los resultados obtenidos durante la investigación y desde el enfoque cualitativo, se fundamenta en una perspectiva interpretativa centrada en el entendimiento del significado de las acciones, buscando interpretar los resultados obtenidos al contexto del problema estudiado. La importancia de determinar el análisis de rentabilidad parte de las múltiples metas de las empresas, sean las que se basan en utilidad, o las que se basan en la estabilidad, el desarrollo o el servicio a la comunidad, el análisis de beneficios, la disputa tiende a estar en el centro de la discusión como toda una variable fundamental de la actividad económica.
Keywords: CONTROL DE COSTOS; PRODUCCION; SECTOR CAMARONERO; RENTABILIDAD